Occupational Stress And Burnout Among Clinical Nursing Teachers - Mimi Syuhada, Shaifol Anuar (2025)
Teaching nursing students in a clinical setting presents difficulties and conflicts for clinical nursing teachers. They might be experiencing stress at work, which might result in burnout. This study is to determine the level factors associated with occupational stress, determine the level of occupational burnout among clinical nursing teachers and relationship between factors of occupational stress and occupational burnout, as well as explore the significant contributing factors of occupational burnout among clinical nursing teachers. A cross-sectional study design and convenience sampling was conducted. A total of 61 clinical nursing teachers from 3 institutions. Used the Chinese version of the job content questions and occupational burnout inventory to collect data. Pearson’s correlation was used to determine the contributing factors of occupational burnout. Pearson’s correlation analysed showed that the factors of occupational stress such as job control, workplace relationship, and workplace support were significant predictors of occupational burnout. Workplace support was the strongest contributing factors that lead to occupational burnout explained the p-value = 0.011, while the weak factors that contributing to burnout is workload that explained by the p-value = 0.797. Job control, workplace relationship, and workplace support influence occupational burnout. This study results may help administrators recognize the vulnerability of clinical nursing teachers to different stressors and develop strategies to improve occupational burnout.